2022
DOI: 10.1016/j.jaci.2021.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Allergoid–mannan conjugates reprogram monocytes into tolerogenic dendritic cells via epigenetic and metabolic rewiring

Abstract: DCs: Dendritic cells; SOCS: Suppressor of cytokine signaling; HDACs: Histone deacetylases;Mannan-tolDCs: Tolerogenic DCs generated by allergoid-mannan conjugates Allergoid-mannan conjugates reprogram monocytes into tolerogenic DCsT cell naïve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…In this study, we initially sought to assess the potential capacity of the synthetic cannabinoid WIN55212‐2 to interfere with the polarizing effects imprinted by CPE on human DCs. For that, we employed a well‐defined co‐culture experimental model of hmoDCs and allogeneic naïve CD4 + T cells, which allowed us to study how human DCs condition T‐cell polarization in a non‐antigen‐specific manner 33–35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we initially sought to assess the potential capacity of the synthetic cannabinoid WIN55212‐2 to interfere with the polarizing effects imprinted by CPE on human DCs. For that, we employed a well‐defined co‐culture experimental model of hmoDCs and allogeneic naïve CD4 + T cells, which allowed us to study how human DCs condition T‐cell polarization in a non‐antigen‐specific manner 33–35 …”
Section: Discussionmentioning
confidence: 99%
“…the synthetic cannabinoid WIN55212-2 to interfere with the polarizing effects imprinted by CPE on human DCs. For that, we employed a well-defined co-culture experimental model of hmoDCs and allogeneic naïve CD4 + T cells, which allowed us to study how human DCs condition T-cell polarization in a non-antigen-specific manner [33][34][35]. WIN55212-2 significantly impairs the expression of costimulatory molecules and proinflammatory cytokines induced by CPE-stimulated hmoDCs.…”
mentioning
confidence: 99%
“…14 In addition of being hypoallergenic, 14,15 PM-allergoids target dendritic cells by binding to C-type lectin receptors through their mannan moiety, which are rapidly and efficiently taken up by these cells. 16,17 Preclinical data indicate that PM-allergoids induce tolerogenic dendritic cells and macrophages capable of promoting Treg-cell responses in vitro 15,[18][19][20] and in vivo, whether administered subcutaneously (SC) 15,20 or sublingually (SL), 17 thus, with promising potential for AIT. 21 A pilot study in veterinary medicine indicated that SC immunotherapy with PM-allergoids (D. farinae) was safe and successful in the treatment of canine atopic dermatitis.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…2,3 We recently demonstrated that PM reprogram monocytes from healthy donors and allergic patients into tolerogenic DCs via epigenetic and metabolic reprogramming. 4 However, their capacity to regulate macrophage polarization remains unknown. Macrophages (MØ) exhibit sufficient cell plasticity to be able to polarize into different phenotypes, from pro-inflammatory, pathogen-eliminating, and subsequent tissue-damaging to antiinflammatory or more regulatory profiles.…”
Section: Allergoid-mannan Conjugates Imprint Tolerogenic Features In ...mentioning
confidence: 99%
“…Cluster analysis is a popular unsupervised machine learning (ML) method for discovering previously undetected data patterns. 4 ML-based cluster analysis has been used in several diseases for the identification and characterization of patient subgroups. 5,6 As of now, no study has attempted to identify CU subtypes with this method.…”
Section: S U Pp O Rti N G I N Fo R M Ati O Nmentioning
confidence: 99%